Daily Behaviour of Long-tailed Macaque in the Captive, Semi-wild, and Wild Habitats: Preliminary Reports (Indonesian Journal of Primatology, 2022)
One of the endangered non-human primates, Macaca fascicularis, can adapt to various conditions of habitats, including full-housed, semi-wild, and natural habitats. This species has multi-male, multi-female social bonds that influence their daily behaviour activity. This study tried to describe the daily behaviour of Macaca fascicularis in their original habitats through a web-based survey. This study categorised the original habitat as captive, semi-wild, and wild. The focus of behavioural frequency data observed in all habitats includes feeding, locomotion, sleeping, grooming, playing, and aggression. This study used statistical analysis for each paired habitat. The daily behaviour for all pairs showed similar budgets, except for captive 1 and 2, which showed significant differences (p-value